2011
DOI: 10.2113/econgeo.106.5.809
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Exploration for Gold Through Transported Alluvial Cover in Nevada: Examples from the Cortez Mine

Abstract: Geochemical orientation surveys were completed over covered Carlin-type gold deposits in the Cortez mine area with the expressed aim of identifying and evaluating exploration methods to discover Au ore under transported alluvial cover in Nevada. Orientation tests were designed to assess the utility of geochemical applications at various scales of exploration, both drill targets at the deposit scale and "footprints" associated with deposits at the district scale. Detailed surveys were completed over the covered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Difference in aqueous species migration in the reduced column compared to its surroundings is also proposed for explaining the anomalous element concentration "rabbit-ear" pattern measured in soils (Smee, 1984). High CO 2 and CH 4 concentration and low O 2 concentration anomalies in soil air are known as markers of concealed mineralization (McCarthy et al, 1986;Pauwels et al, 1999;Lovell, 2000;Zhang, 2000;Polito et al, 2002;Muntean and Taufen, 2011). These anomalies have been related to the release of gas during fluid inclusion breakdown, biological respiration and to the alteration of the carbonate gangue.…”
Section: Model Of H 2 Production During Gold Deposit Alterationmentioning
confidence: 99%
“…Difference in aqueous species migration in the reduced column compared to its surroundings is also proposed for explaining the anomalous element concentration "rabbit-ear" pattern measured in soils (Smee, 1984). High CO 2 and CH 4 concentration and low O 2 concentration anomalies in soil air are known as markers of concealed mineralization (McCarthy et al, 1986;Pauwels et al, 1999;Lovell, 2000;Zhang, 2000;Polito et al, 2002;Muntean and Taufen, 2011). These anomalies have been related to the release of gas during fluid inclusion breakdown, biological respiration and to the alteration of the carbonate gangue.…”
Section: Model Of H 2 Production During Gold Deposit Alterationmentioning
confidence: 99%
“…Detailed studies of ore-stage arsenian pyrite show that trace element and sulfur isotope zoning formed from temporally discrete ore fluids fed by separate structures (Barker et al, 2009;Longo et al, 2009;Muntean et al, 2009). Recent research also focused on enlarging the target for Carlin-type gold deposits by looking for zoning patterns surrounding Carlin-type gold deposits, including lithogeochemistry (Patterson and Muntean, 2011) and halos of depleted δ 18 O in carbonate oxygen isotopes (Barker et al, 2013;Hickey et al, 2014a;Vaughan et al, 2016), as well as signatures in transported alluvial and sedimentary cover and groundwater (Muntean and Taufen, 2011;Cluer, 2012). In chapter 2, Muntean (2018) presents a mineral systems approach to exploring for Carlintype gold deposits in Nevada.…”
Section: Overview Of the Volumementioning
confidence: 99%
“…For example, Alpers et al (1990) studied the stable isotopic composition of soil CO 2 over the Crandon deposit and found that anomalous concentrations reported by McCarthy et al, (1986) were derived from root respiration rather than from mineralization. Despite the complex and multiple origins of soil gases, numerous gas species (e.g., CO 2 , O 2 , Hg, Rn, He, sulfur compounds, and light hydrocarbons) appear to be related to buried mineral deposits (Carr et al, 1986;Klusman, 1993;Hale, 2000;Pauwels et al, 1999;Polito et al, 2002;Klusman, 2009;Muntean and Taufen, 2011;Noble et al, 2013). Specific ore bodies have been shown to contain varying amounts of light hydrocarbons having C chains of C 1 -C 9 and include methane, ethane and propane (Disnar, 1990;Hulen and Collister, 1999;Polito et al, 2002).…”
Section: Gaseous Dispersionmentioning
confidence: 99%